Model Bimbingan Keagamaan terhadap Anak-Anak Karyawan Perkebunan Sawit - Nasution, Inez Echa Aurel; Sahrul, Sahrul (Institut Agama Islam Sunan Giri Ponorogo, 2026)
his study examines how religious guidance method at Muhammadiyah Islamic Junior High School Simpang Empat Marbau, Labuhan Batu Utara. This research takes a descriptive qualitative approach. The research informants consisted of three individuals, namely the principal and two Islamic Religious Education teachers who were directly involved in implementing religious guidance activities at the school. Data collection techniques included semi-structured interviews, observation, and documentation. The research team applied the Miles and Huberman interactive analysis technique, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the religious guidance method implemented for the children of palm oil plantation employees at Muhammadiyah Islamic Junior High School Simpang Empat Marbau mainly applies the habituation method. This method is carried out through several structured religious activities, such as religious lectures (kultum), Al-Qur’an memorization, congregational Dhuha and Dhuhur prayers, and an overnight faith and piety development program (mabit) conducted every semester. In addition, teachers provide continuous supervision and motivation to strengthen students’ religious awareness and discipline. This approach not only clarified the findings but also fostered students’ monotheistic values, strengthened their worship discipline, boosted self-confidence, and encouraged responsibility and respect for parents, teachers, and peers in everyday interactions.